2013
DOI: 10.1186/2049-6958-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid function on COPD exacerbation frequency: a preliminary study

Abstract: BackgroundFrequent exacerbations of chronic obstructive pulmonary disease (COPD) have negative effects on quality of life and survival. Thus, factors related to exacerbations should be determined. We aimed to evaluate the effects of thyroid function on quality of life and exacerbation frequency in COPD patients.MethodsThe study population (n = 128) was divided into 3 groups (Group 1: COPD patients with hypothyroidism (n = 44); Group 2: COPD patients with normal thyroid function tests (n = 44); Group 3: Healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
2
16
0
7
Order By: Relevance
“…Another study also confirmed lower values of MEP in COPD patients with hypothyroidism than in those without this condition [31]. The authors observed significantly lower values of FVC, FEV 1 /FVC, forced expiratory flow at 25 and 75% (FEF25-75%) in this group of patients [31]. Others reported on correlation between MEP and MIP values and thyroid function [2].…”
Section: Hypothyroidismsupporting
confidence: 60%
See 4 more Smart Citations
“…Another study also confirmed lower values of MEP in COPD patients with hypothyroidism than in those without this condition [31]. The authors observed significantly lower values of FVC, FEV 1 /FVC, forced expiratory flow at 25 and 75% (FEF25-75%) in this group of patients [31]. Others reported on correlation between MEP and MIP values and thyroid function [2].…”
Section: Hypothyroidismsupporting
confidence: 60%
“…The association of free T3 (fT3) level with arterial blood gases and pulmonary function parameters (vital capacity [VC] or forced vital capacity [FVC], FEV 1 , peak expiratory flow [PEF]) has been demonstrated [14]. Another study also confirmed lower values of MEP in COPD patients with hypothyroidism than in those without this condition [31]. The authors observed significantly lower values of FVC, FEV 1 /FVC, forced expiratory flow at 25 and 75% (FEF25-75%) in this group of patients [31].…”
Section: Hypothyroidismsupporting
confidence: 58%
See 3 more Smart Citations